Legislation on Agrivoltaics in Germany: Changes and Complements Towards a Comprehensive Legal Framework - Max Trommsdorff; Jens Vollprecht; Till Sterzenbach (AgriVoltaics Conference Proceedings)
Following the authors’ two contributions “Legal Framework of Agrivoltaics in Germany” [1] and “New Legal Framework of Agrivoltaics in Germany” [2] in previous proceedings of the AgriVoltaics conference series, this study summarizes changes of and complements to the legal framework for agrivoltaics in Germany that have been implemented after April 2023. The changes and complements relate to the public and energy law and represent major and important improvements for agrivoltaics towards a comprehensive legislation. In the public law, a new legislation on building permits privileges small agrivoltaic facilities leading to an easier and faster permitting procedure compared to those of larger facilities. In the energy law, a new amendment to the Renewable Energy Act (German: Erneuerbare-Energien-Gesetz, EEG) provides more attractive feed-in tariffs for certain agrivoltaic systems. Also, the amendment includes a mandatory level of ecosystem services provisions for conventional ground-mounted photovoltaic systems (GMPV), hence, levering the ecologic potential of a dual land use with PV systems. Finally, the authors present the new German pre-standard DIN 91492 that specifies requirements for agrivoltaics with animal husbandry which might provide a definition for legislators in Germany they can refer to. While the adjustments to the legal framework represent important steps towards a broad market entry of agrivoltaics, challenges remain a sufficiently differentiated framework that considers the specific cost and synergies of the respective agricultural application areas.